ECOLOGICAL STANDARDIZATION AND CIVIL PROTECTION MANAGEMENT UNDER MARTIAL LAW AT CRITICAL INFRASTRUCTURE FACILITIES - Perkun , I. V.; Pogrebnyak , V. G.; Tsymbal , B. M.; Pogrebnyak , A. V. (Systems and Technologies, 2026)
Relevance. Under the conditions of full-scale armed aggression against Ukraine, the anthropogenic load on the natural environment has undergone fundamental and catastrophic changes. The traditional planned technogenic impact has transformed into chaotic, massive, and highly toxic pollution of a multimedia nature. In such conditions, the existing static system of ecological standardization, based on sanitary and hygienic maximum permissible concentrations (MPC) and maximum permissible emissions (MPE), has proven methodologically incapable of effectively responding to unpredictable challenges. This creates a critical gap in the national life safety system and limits the ability of civil protection (CP) units to implement scientifically sound operational management of ecological and technogenic risks during the mitigation of attacks on critical infrastructure facilities. Goal. To develop and scientifically substantiate innovative methodological approaches for adapting the anthropogenic load standardization system, as well as to create a conceptual model for its integration with civil protection management mechanisms under martial law and post-conflict recovery (using the example of the oil and gas industry). Methodology. The study utilizes a comprehensive approach combining systemic and risk analysis methods, the theory of territorial ecological capacity, the concept of socio-ecosystem resilience, and principles of mathematical modeling of pollutant dispersion in the atmosphere. Results. The fundamental necessity of implementing flexible, multi-level standardization tools has been proven. The implementation of a mechanism for temporary emergency standards (MPC-EMERGENCY), adapted similarly to international AEGL and ERPG standards, is proposed for use directly in active combat zones and areas of critical infrastructure damage. A concept of a unified digital management contour has been developed, in which real-time local environmental monitoring data, processed using geographic information systems (GIS) and artificial intelligence (AI) algorithms, serve as automatic triggers for activating specific CP protocols (evacuation, sheltering, zone isolation). Additionally, the concept of transitional standardization (MPC-TRANSITION) for the safe management of destruction waste and land reclamation is substantiated. Conclusions. It is proven that adaptive ecological standardization must evolve from a passive tool for recording environmental damage into a proactive, preventative management mechanism within the civil protection system. Integrating ecological criteria into safety protocols will minimize sanitary and hygienic losses among the population and rescuers, and ensure the sustainable post-conflict recovery of territories in accordance with European “Build Back Better” principles